Prediabetes and Diabetes Alert : Check Your Blood Glucose - Tunggal Mutika, Winnie; Lisa, Mona (Universitas Mulawarman, 2025)
The risk factors for prediabetes and type 2 diabetes mellitus (T2DM) are known and simple to assess. A strong chain of evidence exists for the benefıts of early identifıcation of and intervention on prediabetes and diabetes. This study aimed to determine the characteristics of patients with prediabetes and T2DM in public health center, Depok, West Java. The study’s characteristics were age, sex, impaired fasting glucose (IFG), and impaired glucose tolerance (IGT). The study design uses descriptive studies. The study population was all people with diabetes mellitus is one in the public health center, Depok, West Java. This study sample was people who checking blood glucose in January 2020 to April 2021 in the public health centers, 238 patients. The sampling technique is by using non-random sampling. The results showed that people aged over 55 years 55.5%, female sex 67.2%, based on IFG 42.8% with type 2 diabetes mellitus and 32.4% with prediabetes, based on IGT 27.3% with T2DM and 11.8% with prediabetes. The study population’s conclusions were all people with prediabetes and diabetes mellitus in the public health center, Depok, West Java, aged over 55 years, female sex, IFG, and IGT.